Effect of foot reflexology with auriculotherapy on pain after elective cesarean section: A Randomized Clinical Trial - Elham Khloobagheri; Majid Kazemi; Marzeyeh Loripoor; Babak Bakhtar (Mashhad University of Medical Sciences, 2020)
Introduction: Cesarean section is considered as one of the most common gynecological surgeries. Pain after cesarean section can cause adverse effects to the mother. This shows the need to pay more attention to complementary therapies to reduce pain. Since prioritizing and evaluating the effectiveness of complementary therapies is of great importance, so this study was performed with aim to compare the effects of foot reflexology and auriculotherapy on pain after selective cesarean section. Methods: This randomized controlled clinical trial was performed on 168 cesarean candidates referred to teaching health centers of Rafsanjan University of Medical Sciences in 2018. The subjects were randomly assigned into 3 groups of reflexology, Auriclotherapy and control. Reflexology was performed twice in 24-hour interval and Auriculothera was performed continuously for 24 hours. In the control group, only the researcher was present without intervention. Data collection tools were demographic data form and VAS. Data were analyzed by SPSS software (version 21), and using one-way ANOVA and Tukey Multiple Comparison Test. p < 0.05 was considered statistically significant. Results: Mean pain intensity changes in the foot reflexology group (1.86±1.62) immediately after each intervention were lower than uriclotherapy group (1.45 ± 1.98) and the control group (0.64 ± 2.08) )p < 0.001). But in the uriclotherapy group, pain severity in the interval between the interventions was significantly decreased compared to the reflexology group. Conclusion: Foot reflexology was effective on immediate and short-term pain after cesarean section, and the effect of uriclotherapy with continuous stimulation of the shenmen point is more gradual and lasting. This reduced the need for analgesic use in the uriclotherapy group compared to other groups. Therefore, these two methods can be recommended to relieve pain in post-cesarean care.